The effect of somatostatin analogue (SMS 201-995) on renal function in patients with decompansated cirrhosis and helathy volunteers - Mustafa ÇETİNER and Ercüment OVALI and Yıldız YİĞİTER and Sait KAPICIOĞLU (Turkish Journal of Gastroenterology, 2019)
-